Perspectives of interpersonal interventions at conferences to promote broader inclusion - Smith-Keiling, Beverly L.; Keiling, Andreas (Frontiers in Astronomy and Space Sciences, 2023)
Conferences require a variety of interpersonal interactions starting with conference inception, leadership development, and progressing through organization, the dynamics of invitation, and participation. Thoughtful reasoning along with social connections at the interpersonal level are exemplified in the conference setting where ideas are exchanged and knowledge is shared. This engagement within a welcoming (warm) climate that promotes all voices being heard is essential in broadening inclusion for developing and recognizing a diverse cadre of scientists. Broader inclusion at the interpersonal level can be examined by applying the framework of the Social Cognitive Theory, which considers interpersonal interactions based on many individual personal factors while engaging in an environment and impacting behavior. In this perspective, we share anecdotal experiences from our own involvement hosting (together with colleagues) four small, topically-focused Chapman conferences between 2011-2016 as part of the American Geophysical Union (AGU). In order to promote broader inclusion and ethnographically observe outcomes in the conference environment, we looked retrospectively at interactions of organizing leadership and participants with respect to diversity, e.g., geographical and cultural diversity, perceived gender, ableism and disability. Focusing on interpersonal relationships within the conference environment, we highlight where interpersonal interactions and the climate that results can impact inclusive behavior. It is through observation and recognizing the successes and pitfalls that we identified potential key intervention targets.